DS-CDMA with diversity combining reception in a multipath fading environment - Wu, Shi Ying. (2009)
Performance of a DS-CDMA communication system with diversity combining techniques in a multipath fading environment is studied in this thesis. With noncoherent demodulation of DPSK signaling and equal gain combining (EGC) of multipath diversity, DS-CDMA communication over a frequency selective multipath Rayleigh fading channel is investigated. Numerical results show that the more severe the multipath fading is, the more diversity improvement will be. It is also found that a large number of multipath is beneficial if they are all resolved and exploited in a diversity combining reception. For a small number of multipath, antenna diversity must be employed to improve the bit error rate (BER) performance of the system.